2012
DOI: 10.18061/dsq.v32i3.3269
|View full text |Cite
|
Sign up to set email alerts
|

From Phantoms to Prostheses

Abstract: <p>Colombia, a country at war for over fifty years, has one of the highest rates of landmine injuries in the world.&nbsp; For decades, landmine victims have remained outside the nation&rsquo;s popular consciousness.&nbsp; Today, landmines and rehabilitative medicine profoundly shape public life. This article shows how the seemingly mundane activity of walking becomes a strangely familiar experience among amputees and an increasingly technical one among medical practitioners in Colombian rehab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Several articles in this collection also enhance the growing scholarly attention to the bodily entanglement between disability and war (see Cohen 2012;Wool 2015;Aciksoz 2019;Pinto-García 2019). They point out the irony that bodily injury created by war, once codified as disability, is seen to benefit from the advances in biomedical, infrastructural, and institutional resources in turn funded by the military in the name of rehabilitation, restitution, and redress.…”
Section: Bodies In Timementioning
confidence: 93%
See 1 more Smart Citation
“…Several articles in this collection also enhance the growing scholarly attention to the bodily entanglement between disability and war (see Cohen 2012;Wool 2015;Aciksoz 2019;Pinto-García 2019). They point out the irony that bodily injury created by war, once codified as disability, is seen to benefit from the advances in biomedical, infrastructural, and institutional resources in turn funded by the military in the name of rehabilitation, restitution, and redress.…”
Section: Bodies In Timementioning
confidence: 93%
“…1 Feminist research at the intersection of anthropology, science and technology studies, and environmental humanities has brought attention to the material legacies of warfare and militarized logics. Adopting an intersectional approach, this scholarship has reflected on multilayered impacts of war technologies and practices on socionatural arrangements including bodies (Cohen 2012;Wool 2015;Aciksoz 2019;Pinto-García 2019), lands (Coates 2016;Kim 2016;Touhouliotis 2018;Henig 2019), environments (Sloterdijk 2009;Nixon 2011;Neimanis 2018), ecopolitical relations (Navaro-Yashin 2009; Krupar 2013), and biomedical knowledge production (Terry 2017;Brandt 2013). These studies have also shown that the creations and remnants of militarization infuse our everyday life, even when "war is (viewed) at a distance" (Kaplan 2018), we are in peacetime, or postconflict scenarios (Nelson 2019;McAllister and Nelson 2013; Berman-Arévalo and Ojeda 2020).…”
Section: Hope In the Darkmentioning
confidence: 99%
“…This temporality is crucial to understanding the material and affective capacity of the artefacto explosivo improvisado. As I will illustrate throughout the article, landmines' power exceeds their capacity to maim soldiers and villagers in times of war and of socalled postwar (Cohen 2015(Cohen , 2012Counter 2018;Franco Gamboa 2013). Active even in their explosive ineffectiveness, they produce political and ecological relationships marked by suspense, uncertainty, and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…The focus on these two sites contributes also to the empirical literature: First, our review for this paper displayed a dearth of research analysing rehabilitation for distinct impairment groups simultaneously. Second, existing literature on amputation‐related rehabilitation is relatively limited and derives mainly from medical and rehabilitation sciences (exceptions include Cohen, 2012; Messinger, 2003; NiMhurchadha et al, 2013). Third, there is extensive research on neurological rehabilitation.…”
Section: Introductionmentioning
confidence: 99%